Manipulation of Dysfunctional Spinal Joints Affects Sensorimotor Integration in the Pre-fontal Cortex: A Brain Source Localization Study - Lelic, D; Niazi, IK; Holt, K; Jochumsen, M; Dremstrup, K; Yielder, P; Murphy, B; Drewes, AM; Haavik, H (Hindawi, 2016)
Objectives. Studies have shown decreases in N30 somatosensory evoked potential (SEP) peak amplitudes following spinal manipulation (SM) of dysfunctional segments in subclinical pain (SCP) populations. This study sought to verify these findings and to investigate underlying brain sources that may be responsible for such changes. Methods. Nineteen SCP volunteers attended two experimental sessions, SM and control in random order. SEPs from 62-channel EEG cap were recorded following median nerve stimulation (1000 stimuli at 2.3 Hz) before and after either intervention. Peak-to-peak amplitude and latency analysis was completed for different SEPs peak. Dipolar models of underlying brain sources were built by using the brain electrical source analysis. Twoway repeated measures ANOVA was used to assessed differences in N30 amplitudes, dipole locations, and dipole strengths. Results. SM decreased the N30 amplitude by 16.9 ± 31.3% (𝑃 = 0.02), while no differences were seen following the control intervention (𝑃 = 0.4). Brain source modeling revealed a 4-source model but only the prefrontal source showed reduced activity by 20.2 ± 12.2% (𝑃 = 0.03) following SM. Conclusion. A single session of spinal manipulation of dysfunctional segments in subclinical pain patients alters somatosensory processing at the cortical level, particularly within the prefrontal cortex.